New species and new records of hybotid dance flies (Diptera: Hybotidae: Tachydromiinae) from Iranian mangrove habitats - Igor V. Shamshev; Ebrahim Gilasian (Journal of Insect Biodiversity and Systematics)
The family Hybotidae (Insecta: Diptera, Empidoidea) is recorded for the first time from mangrove habitats in Iran (Hormozgan Province). Four species belonging to the subfamily Tachydromiinae have been found of which two species are recorded for the first time from the territory of Iran: Crossopalpus subaenescens Collin, 1960 (broadly distributed over the Middle East) and Elaphropeza feminata Shamshev & Grootaert 2007 (known only from mangroves of Singapore). In addition, E. feminata is newly recorded species for the Palaearctic Realm. Two species are described and illustrated as new to science: Drapetis hormozganiensis sp. nov. and Elaphropeza marduoensis sp. nov. The mangrove habitats in Iran do not consist of high hybotid species richness comparing with the high diversity of this family in mangroves of tropical areas. Morphologically, recorded species of Crossopalpus and Drapetis have the closest allies amongst the Palaearctic species. However, the species of Elaphropeza is closely related to the known Oriental species (primarily from Singapore).